2004
DOI: 10.1345/aph.1d230
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Pulmonary Function in Asthma and COPD: Point-of-Care Testing

Abstract: Despite recent advances in medical technology, monitoring of asthma and COPD has not changed significantly. PFTs continue to be the gold standard for evaluating airway obstruction and/or restriction. Clinical trials that will evaluate outcomes such as decreased number of hospitalizations, emergency department visits, unscheduled visits to physicians, and days absent from school or work are needed to determine the utility of new monitoring technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
0
17
0
5
Order By: Relevance
“…Furthermore, linking dyspnea as a quantitative outcome to other important clinical endpoints, such as the 30-day mortality and heart failure re-hospitalization rates, was consistent with suggested developments of dyspnea measurements (4). PEFR, an effort-dependent measure of airflow limitation, was chosen for its portability and strong evidence base in the respiratory literature (12,13). In the cardiac literature, its utility as a diagnostic tool to differentiate cardiac versus respiratory dyspnea has been suggested in some smaller studies (14 -16).…”
mentioning
confidence: 99%
“…Furthermore, linking dyspnea as a quantitative outcome to other important clinical endpoints, such as the 30-day mortality and heart failure re-hospitalization rates, was consistent with suggested developments of dyspnea measurements (4). PEFR, an effort-dependent measure of airflow limitation, was chosen for its portability and strong evidence base in the respiratory literature (12,13). In the cardiac literature, its utility as a diagnostic tool to differentiate cardiac versus respiratory dyspnea has been suggested in some smaller studies (14 -16).…”
mentioning
confidence: 99%
“…These limitations preclude the authors from determining how many patients were lost to enrollment. Although peak flow meters are easy to use and interpret, a major limitation to their use is that results are dependent on patients' understanding and effort [3, 5]. …”
Section: Discussionmentioning
confidence: 99%
“…Peak expiratory flow meters are small, inexpensive, and accessible devices used to measure the peak expiratory flow rate (PEFR) after maximal inspiration. They are commonly prescribed for asthma patients but have shown promise in assessing COPD [4, 5]. Peak expiratory flow is not part of the standard protocol for gauging CHF patients, although several studies have suggested that PEFR may be useful in helping to differentiate cardiac from pulmonary causes of dyspnea [3, 5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent advances in medical technology, monitoring of asthma and COPD has not changed significantly [2]. The diagnosis and staging of these diseases and the assessment of the degree of airflow limitation relies on parameters measured on patients through spirometry, a procedure that requires the measurement of airflow and volume during the execution of a correctly-performed maximal expiratory maneuver.…”
Section: Introductionmentioning
confidence: 99%